Refractory status epilepticus: Febrile Illness Related Epileptic Syndrome (FIRES) - Sharma, Varun Kumar; Hegde, Anaita Udwadia; Nabi, Fazal (International Journal of Epilepsy, 2015)
In recent literature, a new entity has emerged, which focuses on a possible non-encephalitic epileptic encephalopathy precipitated by fever in a previously normal child. We report a typical case of Febrile illness related epileptic syndrome (FIRES) from Indian subcontinent. The index case presented with fever and multiple seizures, which progressed to status epilepticus and encephalopathy. All infectious, metabolic and autoimmune markers were negative. Convulsions were refractory to all possible treatment except thiopentone which achieved burst suppression pattern. Breakthrough seizures were prevented by using lacosamide and ketogenic diet along with multiple anticonvulsants. At 1-year follow-up, patient had a relatively good neurological outcome, however has persistent refractory epilepsy.
Keywords: Refractory epilepsy; FIRES; Ketogenic diet; Lacosamide